The complex relationship between asset wealth, adaptation, and diversification in tropical fisheries. (15th October 2021) - Taylor, Sarah F.W.; Aswani, Shankar; Jiddawi, Narriman; Coupland, Jack; James, Phillip A.S.; Kelly, Stephen; Kizenga, Hellen; Roberts, Michael; Popova, Ekaterina
Abstract: Marine small-scale fisheries are complex social and ecological systems that are currently pressurised by climate change, increasing demand for food, and expectation to sustain livelihoods. Species diversification and occupational diversification are often offered as adaptation strategies to increase the resilience of these fisheries to natural and economic shocks. However, little is known about the nature of species diversification within marine tropical fisheries. Based on 293 interviews with artisanal fishers from six coastal communities located at the isles of Zanzibar, Pemba, Mafia, and Mainland Tanga in Tanzania - we assess if fishers with the highest level of species diversification are the most financially secure and able to adapt to changes in the fishing industry. By creating an Asset Wealth Index (AWI) based on a Multiple Correspondence Approach (MCA), we investigate the relative levels of adaptive capacity and fishery connectivity within the different regional wealth quartiles. We find that less wealthy fishers target fewer species, making them less able to absorb changes in management measures focused on species, area, and closures. Likewise, fishers with higher wealth scores and higher adaptive capacity are able to better absorb the short-term losses of fisheries closures when compared to those with lower wealth and adaptive scores reliant on higher levels of fishery connectivity. Graphical abstract: Image 1 Highlights: Construction of Asset Wealth Index for Tanzanian Small-Scale Fisheries based on a Multiple Correspondence Approach. Less wealthy fishers target fewer species and are less able to absorb changes in management measures such as closures. Wealthier fishers with high adaptive capacity are able to better absorb the short-term losses of fisheries closures.